The Students' Vocabulary Mastery: Mnemonic or Translation Technique - Nike Widia; Ikariya Sugesti; Sirniawati (English Language Education Department, Universitas Majalengka, 2025)
This study explores the comparative effectiveness of mnemonic techniques versus translation methods in enhancing vocabulary mastery among students learning English as a Foreign Language (EFL). A common issue faced by EFL learners is limited vocabulary knowledge, which impedes their ability to follow teacher instructions and complete classroom tasks effectively. Mnemonic techniques, which leverage associative memory and repetition, are posited to enhance vocabulary retention and understanding more efficiently than conventional translation approaches. A quantitative research methodology was employed, utilizing a quasi-experimental design. The participants consisted of seventh-grade junior high school students, assigned to two groups: the experimental group, taught using mnemonic techniques, and the control group, instructed through translation techniques. Vocabulary mastery was assessed using pre-tests and post-tests administered before and after the intervention. The findings revealed a significant improvement in the vocabulary scores of the experimental group, with an average increase of 25.42 points, compared to a 10.88-point gain in the control group. These results indicate that mnemonic techniques are more effective in improving vocabulary mastery, particularly among beginner-level EFL learners.